Farmers’ perception about major insect pests of cucurbits and their management in Arghakhanchi, Nepal - Parajuli, Nikita; Khanal, Kapil; Nepal, Anish; Bastakoti, Bipin (Journal of Agriculture and Natural Resources, 2023)
Cucurbits are important vegetable crops widely cultivated in subtropical and tropical regions, including Arghakhanchi, Nepal. To understand farmers' perceptions on major insect pests of cucurbits and their management in this region, a survey was conducted from February 2023 to May 2023 in Sandhikharka municipality and Chhatradev rural municipality, involving 110 selected respondents applying a stratified random sample method. Data were gathered through focus group discussions (FGD), key informant interviews (KII), and preliminary field visits. Secondary data were collected and analyzed. The results revealed that farmers ranked insect pests and diseases as their most severe problem, with an index value of 0.892, while climate change was the least severe, with an index value of 0.337. Red pumpkin beetle was identified as the most severe insect pest at the seedling (69.1%) and vegetative stages (50.9%), while fruit flies were most severe at the fruiting stage (79.1%). The 67.3% of the respondents reported a moderately increased occurrence of insect pests compared to past years. Most farmers (90%) relied on chemical pesticides, followed by mechanical, cultural, botanical, and physical methods for pest control. However, only 23.6% of farmers knew about Integrated Pest Management (IPM), with a low level of IPM adoption at 40.9%. The study highlights the potential for enhanced cucurbit production if farmers are provided with IPM knowledge, technical support, and improved irrigation facilities.